Prolonged diabetic ketoacidosis due to SGLT2 inhibitor use and low‐carbohydrate diet. (3rd April 2023) - Mung, Sai Man; Fonseca, Ines; Azmi, Shazli; Balmuri, Laxmi Manohar Rao
Abstract: A 59‐year‐old gentleman was admitted with diabetic ketoacidosis (DKA). His medication history included a sodium‐glucose co‐transporter 2 (SGLT2) inhibitor for the past six years. Relevant history includes undertaking a low‐carbohydrate diet for four months. In hospital he required a fixed rate insulin infusion for 25 hours and variable rate insulin infusion for a total of 32 hours to manage his ketonaemia. He received concomitant dextrose infusion and oral nutritional supplements throughout the course of his admission to replenish the likely depleted glycogen stores in his liver as a result of his diet. The case highlights the importance of identifying DKA early and treating the underlying cause. It also highlights the potential increasing prevalence of ketoacidosis which may occur as more patients are prescribed SGLT2 inhibitors and adhere to carbohydrate‐restricted diets. Copyright © 2023 John Wiley & Sons.